An Ethical and Practical Dilemma: Legalizing the Sale of Human Organs - Alana, Oppermann (Journal of Organ Transplantation, 2024)
There are over 100,000 people waiting for life saving organ transplants in the United States. To put this in perspective, even the largest football stadium in the U.S. could not fit this number of people. In 2021 alone, 6,000 people died while waiting for a transplant. Every day, 17 people die waiting, and every 10 minutes, another person is added to the waiting list (“Organ Donation Statistics,” 2023). These numbers are expected to rise due to the lack of organs available, and the increasing need for organs, especially kidneys.
Keywords: Kidney disease; organ transplantation; legalizing organ sales; organ selling.